Jealousy Reflected at Henrik Ibsen's Hedda Gabler Play(1890):An Individual Psychological Approach - Dyah Tri Utami, Nur'aini; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S., M.Hum (2015)
The research is proposed to analyze the jealousy of Hedda Gabler in Henrik Ibsen's Hedda Gabler by Individual Psychological Approach. The research sets two objectives: the first is to analyze the play in term of structural elements, and the second is to analyze the play based on the Individual Psychological Perspective. This study is qualitative study using the play of Henrik Ibsen's Hedda Gabler as the object of the study. There are two kinds of data source: primary and secondary. The primary data source is the script of the play Henrik Ibsen's Hedda Gabler and the secondary data source is the other sources related to the analysis such as the author's biography, essay, and other literary work, which are related to this study.The method of collecting data in the research is library research. In analyzing the data, the writer employs descriptive analysis. The result of the study shows the following conclusion. Based on Individual Psychological Approach, the Hedda Gabler play shows the jealousy that happened in Hedda as the major character in this play. Keywords: Jealousy, Hedda Gabler, Individual Psychological Approach.